Outcome-Focused Dance Movement Therapy Assessment Enhanced by iPad App MARA - Dunphy, Kim F.; Hens, Tessa (Frontiers in Psychology, 2018)
Healthcare and human services are increasingly required to demonstrate effectiveness and efficiency of their programs. Evaluation processes are more regularly part of activity cycles, with outcomes frameworks underpinning these more often. New approaches to service delivery, such as the National Disability Insurance (NDIS) scheme in Australia, require outcome-focussed planning that is driven by the voices and experiences of clients. Eco-systematic approaches to service delivery and assessment consider the client as part of an interconnected web of stakeholders who all contribute to their therapeutic progress. These developments provide challenges for modalities for which there are not yet agreed outcomes, nor well-developed assessment approaches. Dance movement therapists face particular difficulties in this respect, as they have few well-established assessment tools that are practical for regular use. Few existing dance movement therapy assessment approaches facilitate the involvement of clients and other stakeholders. This article addresses these challenges in reporting the use of iPad app MARA (Movement Assessment and Reporting App) developed for assessment in dance movement therapy. MARA is applied in a program for adults with intellectual disabilities over four months. Two therapists report their experience utilising the app’s features (quantitative scoring, qualitative note-taking, photos and videos) complemented by participants’ reflections on their own progress in words and non-verbal feedback. An example of data generated through MARA and these complementary processes and a progress report for participants and families is provided. Responses to these reports from program stakeholders (twelve participants, twelve families, eleven centre staff) are gathered through interviews and focus groups. Therapists discuss benefits of using MARA as including a sharpened outcome-focus, more consistent and efficient assessment practice, improved planning and decision-making and stronger communication with stakeholders. Families indicate that reports enable better understanding of their family member with intellectual disability’s experience and potential usefulness in informing NDIS service planning. Managers comment on the potential function of such data for quality control and resource decisions, while other staff confirm the therapists’ perspective that such reports offer the possibility of improved communication and collaboration between different programs and their staff, in turn improving integrated service provision and client outcomes.